Rapid Photothermal Responsive Conductive MXene Nanocomposite Hydrogels for Soft Manipulators and Sensitive Strain Sensors. Issue 23 (13th September 2021) - Sun, Zhichao; Song, Changyuan; Zhou, Junjie; Hao, Chaobo; Liu, Wentao; Liu, Hao; Wang, Jianfeng; Huang, Miaoming; He, Suqin; Yang, Mingcheng
Abstract: Stimulus‐responsive hydrogels are of great significance in soft robotics, wearable electronic devices, and sensors. Near‐infrared (NIR) light is considered an ideal stimulus as it can trigger the response behavior remotely and precisely. In this work, a smart flexible stimuli‐responsive hydrogel with excellent photothermal property and decent conductivity are prepared by incorporating MXene nanosheets into the physically cross‐linked poly( N ‐isopropyl acrylamide) hydrogel matrix. Because of outstanding photothermal effect and dispersion of MXene, the composite hydrogel exhibits rapid photothermal responsiveness and excellent photothermal stability under the NIR irradiation. Furthermore, the anisotropic bilayer hydrogel actuator shows fast and controllable light‐driven bending behavior, which can be used as a light‐controlled soft manipulator. Meanwhile, the hydrogel sensor exhibits cycling stability and good durability in detecting various deformation and real‐time human activities. Therefore, the present study involving the fabrication of MXene nanocomposite hydrogels for potential applications in remotely controlled actuator and wearable electronic device provides a new method for the development of photothermal responsive conductive hydrogels. Abstract : Rapid photothermal responsive and conductive MXene nanocomposite hydrogels are used for soft manipulators and sensitive strain sensors.